KEMITRAAN DALAM PENDIDIKAN ANAK USIA DINI (Analisis terhadap Pola dan Tingkah Laku Anak Usia Dini dan Lingkungan) - Hafidzi, Anwar; Putri, Hadisa (Pendidikan Islam Anak Usia Dini (PIAUD) Fakultas Tarbiyah dan Keguruan UIN Antasa, 2018)
Abstract: Partnership is a cooperative relationship between several parties in achieving a certain work relationship. The partnership between the school and the family and community in building an educational ecosystem is in line with the Ministry of Education and Culture's vision of